Tumor Exosomes Induce Tunneling Nanotubes in Lipid Raft-Enriched Regions of Human Mesothelioma Cells - Thayanithy, Venugopal (2014)
Tunneling nanotubes (TnTs) are long, non-adherent, actin-based cellular extensions that act as conduits for transport of cellular cargo between connected cells. The mechanisms of nanotube formation and the effects of the tumor microenvironment and cellular signals on TnT formation are unknown. In the present study, we explored exosomes as potential mediators of TnT formation in mesothelioma and the potential relationship of lipid rafts to TnT formation. Mesothelioma cells co-cultured with exogenous mesothelioma-derived exosomes formed more TnTs than cells cultured without exosomes within 24-48 hours; and this effect was most prominent in media conditions (low-serum, hyperglycemic medium) that support TnT formation (1.3-1.9-fold difference). Fluorescence and electron microscopy confirmed the purity of isolated exosomes and revealed that they localized predominantly at the base of and within TnTs, in addition to the extracellular environment. Time-lapse microscopic imaging demonstrated uptake of tumor exosomes by TnTs, which facilitated intercellular transfer of these exosomes between connected cells. Mesothelioma cells connected via TnTs were also significantly enriched for lipid rafts at nearly a 2-fold higher number compared with cells not connected by TnTs. Our findings provide supportive evidence of exosomes as potential chemotactic stimuli for TnT formation, and also lipid raft formation as a potential biomarker for TnT-forming cells.